Effectiveness of Cutting and Tailoring Trainings Organised by Krishi Vigyan Kendra for Scheduled Caste Women (Indian Journal of Extension Education, 2019)
Cutting and tailoring is one of the avenues for self-employment which require less of basic and technical education, minimum infrastructure and moderate financial needs. Proficiency in the art of cutting and tailoring is an essential pre-requisite in clothing construction, it is very important to know the techniques of cutting and tailoring for producing attractive garments. The present study analyzed the effectiveness of trainings imparted by Krishi Vigyan Kendra, Sadalpur on cutting and tailoring. Among the training programme designing of garment was very useful with maximum training effectiveness index. The training on surface enrichment (83.61) and cutting of garments (82.78) was useful among the respondents with marginally TEI score. Respondents were found to be highly satisfied with raining programme. It indicated that respondents were highly satisfied about the subject matter taught/covered and quality of trainer made available to them during training programme.